The fallacies of regulatory market splits: Network neutrality regulation ante portas - Günter Knieps; Volker Stocker (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2014)
Network neutrality regulations for the Internet have been discussed for about a decade. In Europe, recent efforts have produced a proposal by the European Commission for a network neutrality regulation. Envisaged is the introduction of a two-tiered Internet traffic regulation based on a regulatory market split between the markets for 'public' Internet traffic services and markets for specialized services giving higher and ensured quality of data transmission. We argue that regulatory market splits are artificial and the proposed regulation of markets for Internet traffic services constitutes a regulatory fallacy.
Keywords: 330